Regulatory Analysis Digital Markets Act (Dma) European Union In Business Competition - Nurhayati, Yati (Scholar Center, 2023)
this research aims to analyze the concept of the Business Competition Digital Markets Act (DMA) European Union and analyse the regulation affecting Digital Markets Act (DMA) EU to the digital market. The science of law will have authority and strength if it is integral in ontological, epistemological, and axiological aspects. Normative legal research has the characteristics of library research. The results of this study showThe combination of these three factors to win the competition to win the hearts of consumers can be obtained through innovation, application of the right technology, and managerial ability to direct company resources in winning the competition. In response, the European Commission recently published a proposal for a Digital Markets Act to complement existing competition policy tools through mandatory from before for platforms. Both consumers and companies should benefit from digital markets. However, it may backfire if there are no clear boundaries to follow.